Attachment, Emotion Recognition and Impulsivity: As A Risk of Child Sexual Abuse - Demirci, Esra; Öztop, Didem Behice; Özmen, Sevgi; Özdemir, Çağlar (The Bulletin of Legal Medicine, 2017)
Introduction: It has been reported that certain children are more at risk of sexual abuse: these risks factors are defined as individual, familial, social and institutional factors. Although; data from clinical risks in the literature is limited. In this study, we aimed to determine the clinical risk factors of sexual abuse. Methods: 22 female and 12 male, sexual abused children and 34 healthy volunteer children were involved in this study. Patients and volunteers were assessed with the Parental Bonding Instrument (PBI), Reading Mind from Eyes Test (RMET) and the UPPS impulsive behavior scale. Results: There were no significant differences in maternal attachment scores in either group but the paternal attachment scores were statistically significantly lower in the study group. The RMET scores were statistically significantly lower in the study group than in the control group. The UPPS impulsive behavior scale unpersistence subscores were statistically significantly higher in the study group than in the control group. Conclusion: Sexual abuse is known as the most difficult type of trauma to treat and preventing the risk of identification is of the most importance. Further studies with a large sample are needed to determine the clinical risk factors of sexual abuse.